ASUHAN KEPERAWATAN KELUARGA PADA KASUS POST STROKE DENGAN MASALAH KEPERAWATAN GANGGUAN MOBILITAS FISIK DI DESA BLULUK KABUPATEN LAMONGAN - Endah Sri Wijayanti (Universitas Muhammadiyah Lamongan, 2021)
Introduction : Stroke is brain damage due to blood supply to the brain, often occursSuddenly within 24 hours without realizing it, such as rupture of blaood vessels in the brain and lack og blood supplay in the brain. Prevalence by sex male 11,0%(10,5-11,5 per mile) 355,726 cases, female sex 10,9(10,4-11,4 per mile) 358,056 cases. The proportion of stroke control to health care facilities in the population aged 15 years with routine Esat Java stroke prevalence 40,0% sometimes 39,5 not re-checking 20,5% (Ministry of Health of the Republic of Indonesia, 2018). Methods : This research method uses a case study. Data were collected by means of interviews, aobservations, and documentation studies.Results : The results of the case study indicate a gap in the assessment of nursing care. Nursing diagnoses according to thew IDHS lead to the main priority, namely Mobility Support (D> 0045), priority nursing actions according to SIKI Mobilization Support (I. 05173), with outcomes according to SLKI Physical moboility (L. 05042), evaluation of the main priority diagnoses, namely mobility disorders partially resolved by home visits for 6 days. Discussion : Combination of active and passive Range of Movement technique interventions such as doing wrist range of motion exercises consisting of flexion, which is moving the palm of the hand to the inside of theforearm, extension, which is moving the fingers, hand and forearm are in the same one. Keywords : Stroke,Physical Mobility Disorders, Family Passive ang Active ROM